Comparison of four tools to identify painful new osteoporotic vertebral fractures in the postmenopausal population in Beijing - Guo, SiJia; An, Ning; Lin, JiSheng; Fan, ZiHan; Meng, Hai; Yang, Yong; Fei, Qi (Frontiers in Endocrinology, 2022)
Objectives To validate and compare four tools, the Fracture Risk Assessment Tool (FRAX) without bone mineral density (BMD), Beijing Friendship Hospital Osteoporosis Screening Tool (BFH-OST), Osteoporosis Self-Assessment Tool for Asians (OSTA), and BMD, to identify painful new osteoporotic vertebral fractures (PNOVFs). Methods A total of 2874 postmenopausal women treated from June 2013 to June 2022 were enrolled and divided into two groups: patients with PNOVFs who underwent percutaneous vertebroplasty (PNOVFs group, n = 644) and community-enrolled females (control group, n = 2230). Magnetic resonance and X-ray imaging were used to confirm the presence of PNOVFs. Dual-energy X-ray absorptiometry was performed to calculate the BMD T-scores. Osteoporosis was diagnosed according to WHO Health Organization criteria. Data on the clinical and demographic risk factors were self-reported using a questionnaire. The ability to identify PNOVFs using FRAX, BFH-OST, OSTA, and BMD scores was evaluated using receiver operating characteristic (ROC) curves. For this evaluation, we calculated the areas under the ROC curves (AUCs), sensitivity, specificity, and optimal cut-off points. Results There were significant differences in FRAX (without BMD), BFH-OST, OSTA, and BMD T-scores (total hip, femoral neck, and lumbar spine) between the PNOVFs and control groups. Compared with BFH-OST, OSTA, and BMD, the FRAX score had the best identifying value for PNOVFs; the AUC of the FRAX score (optimal cutoff =3.6%) was 0.825, while the sensitivity and specificity were 82.92% and 67.09%, respectively. Conclusion FRAX may be the preferable tool for identifying PNOVFs in postmenopausal women, while BFH-OST and OSTA can be applied as more simple screening tools for PNOVFs.